A cross-sectional observational study comparing foot and ankle characteristics in people with stroke and healthy controls. Issue 12 (5th June 2017) - Kunkel, Dorit; Potter, Julia; Mamode, Louis
Abstract: Purpose: The purpose of this study was to explore and compare foot and ankle characteristics in people with stroke and healthy controls; and between stroke fallers and non-fallers. Methods: Participants were recruited from community groups and completed standardized tests assessing sensation, foot posture, foot function, ankle dorsiflexion and first metatarsal phalangeal joint range of motion (1st MPJ ROM), hallux valgus presence and severity. Results: Twenty-three stroke participants (mean age 75.09 ± 7.57 years; 12 fallers) and 16 controls (mean age 73.44 ± 8.35 years) took part. Within the stroke group, reduced 1st MPJ sensation ( p = 0.016) and 1st MPJ ROM ( p = 0.025) were observed in the affected foot in comparison to the non-affected foot; no other differences were apparent. Pooled data (for both feet) was used to explore between stroke/control ( n = 78 feet) and stroke faller/non-faller ( n = 46 feet) group differences. In comparison to the control group, stroke participants exhibited reduced sensation of the 1st MPJ ( p = 0.020), higher Foot Posture Index scores (indicating greater foot pronation, p = 0.008) and reduced foot function ( p = 0.003). Stroke fallers exhibited significantly greater foot pronation in comparison to non-fallers ( p = 0.027). Conclusions: Results indicated differences in foot and ankle characteristics post stroke in comparison to healthy controls. These changes may negatively impact functional ability and the ability to preserve balance. Further research is warranted to explore the influence of foot problems on balance ability and falls in people with stroke. Implications for Rehabilitation: Foot problems are common post stroke. As foot problems have been linked to increased fall risk among the general population we recommend that it would be beneficial to include foot and ankle assessments or a referral to a podiatrist for people with stroke who report foot problems. Further research is needed to explore if we can improve functional performance post stroke and reduce fall risk if treatment or prevention of foot problems can be included in stroke rehabilitation.